Preserving the Authenticity of Qirā’āt Sab'ah: A Comparative Study of Musyāfahah Methods at Al-Hasan and Al-Munawwir Boarding School - Roni Susanto; Ahmad Munir; Basuki Basuki (Dialogia, 2025)
This study examines the challenges in maintaining the authenticity of qirā’āt sab’ah in the face of technological advances, focusing on the credibility of the sanad and the originality of the readings. Using qualitative methods, this study compares the application of the musyāfahah method in Al-Hasan Tahfīz Quran Islamic Boarding School, Ponorogo, and Al-Munawwir Tahfīz Quran Islamic Boarding School, Krapyak, Yogyakarta, through interviews with informants, observation, and documentation. The findings of this study revealed three important things: (1) both Boarding Schools have the same qirā’āt sab’ah sanad lineage, which is supported by a syahādah (certificate); (2) Al-Munawwir Boarding School emphasizes credibility and originality through strict standardization, while Al-Hasan Boarding School adopts a more practical and inclusive approach; and (3) the transformation of Al-Hasan Boarding School promotes broader participation, increasing the number of students, while Al-Munawwir Boarding School focuses on cognitive depth through classical musyāfahah phases.   REFERENCES Abidin, Nurul Huda Zainal, Najmiah Omar, and Nor Hafizi Yusof. “Concepts and Implementation of Talaqqi And Musyafahah Methods in Learning the Quran.” Malaysian Journal For Islamic Studies 3, no. 1 (2019): 27–35. https://journal.unisza.edu.my/mjis/index.php/mjis/article/view/81. ABLAY, Rıfat. “Hadis Mecmualarında Yer Alan Kıraate Dair Hadislerin Değerlendirilmesi ve Bu Hadislerin Kıraat İlmindeki Yeri.” Artuklu Akademi 9, no. 1 (2022): 179–96. https://doi.org/10.34247/artukluakademi.1069435. Abuhamdia, Zakaria Ahmad. “Between Veneration for the Text and Vernacularization of the Spoken Form in Quran Recitation.” Journal of Literature, Languages and Linguistics 18 (2016): 44–49. Ahmad, La Ode Ismail, Muhammad Ali, Mirwan Mirwan, Abdul Rahman Sakka, and Risna Mosiba. “Bullying on Social Media: Primitive Behavior Against Prophetic Marchals From A Hadith Ahkam Perspective.” Samarah 8, no. 1 (2024): 79–104. https://doi.org/10.22373/sjhk.v8i1.20189. Ahmed, Dr. Muneer, Dr. Aijaz Ali Khoso, and Muhammad Hammad. “The Efforts of Ulma for the Ilm e Qiraat, &Tajweed in the Indian Subcontinent.” Al Khadim Research Journal of Islamic Culture and Civilization 3, no. 1 (2022): 92–110. https://doi.org/10.53575/arjicc.v3.01(22)a7.92-110. Allison, M, MPH, Schmidt, Leah M., Ranney, Jessica K., Pepper, and Goldstein, Adam. "Source Credibility in Tobacco Control Messaging." Physiology & Behavior 176, no. 5 (2019): 139–48. https://doi.org/10.18001/TRS.2.1.3.Source. Amanda, Salsabila, Hotimin Hotimin, and Mulhendra Mulhendra. “Learning Mahaarah Al-Qiraa’ah Using Hijaiyyah Card Media in Islamic Elementary Schools.” Jurnal Indonesia Sosial Teknologi 5, no. 4 (2024): 1793–97. https://doi.org/10.59141/jist.v5i4.1017. Antoni, A. “Cara Mudah Belajar Islam Dengan Kitab Ta ’Līmush Shibyān Bighāyatil Bayān.” El-Hikam, 2012. http://ejournal.kopertais4.or.id/sasambo/index.php/elhikam/article/view/1441. Arrohman, Syauqu Rofiq, Meti Fatimah, and Uswatun Khasanah. “Implementation Of The Learning Model With The ’Ali Method To Improve The Ability To Read The Qur’an Of Students Of The Special Program For Tahfizhul Qur’an (PKTQ) Sukoharjo 2022/2023 State Madrasah Ibtidaiyah.” AL-WIJDÃN Journal of Islamic Education Studies 7, no. 2 (2023): 304–21. https://doi.org/10.58788/alwijdn.v7i2.2651. Badruddin Muhammad bin Abdullah Az-Zarkasyi. Al-Burhan Fi Ulum Al-Qur’an. Beirut: Daar al-Fikr, 1988. Bizawie, Zainul Milal. Sanad Qur’an Dan Tafsir Di Nusantara (Jalur, Lajur, Dan Titik Temunya). Ciputat: Pustaka Compass, 2022. Boekel, Martin Van, Karla A. Lassonde, Edward J. O’Brien, and Panayiota Kendeou. “Source Credibility and the Processing of Refutation Texts.” Memory and Cognition 45, no. 1 (2017): 168–81. https://doi.org/10.3758/s13421-016-0649-0. CHAHDI, Hassan. “La Canonisation Des Variantes de Lecture Coraniques En Question : Remarques Sur La Mémorisation Intégrale Du Coran et Les Critères de Sélection Des Qurrāʾ.” Archimède. Archéologie et Histoire Ancienne 10 (2023): 60–76. https://doi.org/10.47245/archimede.0010.ds1.05. Chamsi-Pasha, Hassan, and Mohammed Ali Albar. “Ethical Dilemmas at the End of Life: Islamic Perspective.” Journal of Religion and Health 56, no. 2 (2017): 400–410. https://doi.org/10.1007/s10943-016-0181-3. Cicilia, Nathasya Udur. “Peran Kredibilitas Duta Merek Dalam Meningkatkan Efektivitas Iklan.” Jurnal Sosial Dan Humaniora 1, no. 3 (2024): 75–83. https://doi.org/https://doi.org/10.62017/arima.v1i2.623. Darwis Hude, M, Ahsin Sakho Muhammad, and Sasa Sunarsa. “Penelusuran Kualitas Dan Kuantitas Sanad Qiraat Sab’ah: Kajian Takhrij Sanad Qiraah Sab’ah.” Sasa Sunarsa Misykat 05 (2020): 1–22. Fardiah, Fardiah, Santosa Murwani, and Nurbiana Dhieni. “Meningkatkan Kemampuan Kognitif Anak Usia Dini Melalui Pembelajaran Sains.” Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini 4, no. 1 (2019): 133. https://doi.org/10.31004/obsesi.v4i1.254. Fasya, Ali, and Ami Muftil Anami. "Hadis Studies Methodology of Teaching Qiraat Sab ' Ah : An Analysis of KH Muhsin Salim's Approach in the Context of Qur'anic Education Metodologi Pengajaran Qiraat Sab ' Ah : Analisis Pendekatan." Journal of Qur’an and Hadis Studies 5, no. 1 (2024): 109–23. https://doi.org/https://doi.org/10.28918/aqwal.v5i1.7199. Firman, Walni, and La Ode Anhusadar. “Peran Guru Dalam Menstimulasi Kemampuan Kognitif Anak Usia Dini.” Kiddo: Jurnal Pendidikan Islam Anak Usia Dini 3, no. 2 (2022): 28–37. https://doi.org/10.19105/kiddo.v3i2.6721. Gordon, Emma C. “Cognitive Enhancement and Authenticity: Moving beyond the Impasse.” Medicine, Health Care and Philosophy 25, no. 2 (2022): 281–88. https://doi.org/10.1007/s11019-022-10075-2. Hamid, Muhammad, and Syamsul Bakri. “Urgensi Sanad Dalam Meningkatkan Profesionalitas Guru Pendidikan Agama Islam.” Al-Hasanah : Jurnal Pendidikan Agama Islam 8, no. 2 (2023): 344–55. https://doi.org/10.51729/82225. Hovland, C. I., I. L. Janis, and H. H. Kelley. Communication and Persuasion. Yale University Press, 1953. Huberman, A. Michael, and Saldana, Johnny. Qualitative Data Analysis: A Methods Sourcebook. America: Arizona State University, 2014. Hude, M. Darwis, Ahsin Sakho Muhammad, and Sasa Sunarsa. “Penelusuran Kualitas Dan Kuantitas Sanad Qiraah Sab’ah: Kajian Takhrij Sanad Qiraah Sab’ah.” Misykat: Jurnal Ilmu-Ilmu Al-Quran, Hadist, Syari’ah Dan Tarbiyah 5, no. 1 (2020): 1. https://doi.org/10.33511/misykat.v5n1.1-22. Ilmiyah, Dakhirotul. “Hadith Review : The Validity of Ablution for Women Who Wear Waterproof Henna.” El-Buhuth: Borneo Journal of Islamic Studies 7, no. December (2024): 371–82. Istifarin, Nur Annisa, and Ida Rochmawati. “Empirical Experience of the Prophet as a Source of Knowledge Hadith Perspective.” Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, Dan Fenomena Agama 25, no. 1 (2024): 31–44. https://doi.org/10.19109/pgy3s034. Jamil, Ahmad, and Naswan Abdo Khaled. "The Genealogy of Authoritative Transmission of Sanad Al-Qur'an in Java Islamic Boarding Schools." Kalimah: Jurnal Studi Agama Dan Pemikiran Islam 20, no. 2 (2022). https://doi.org/10.21111/klm.v20i2.8332. Jawati, Ramaikis. “Peningkatan Kemampuan Kognitif Anak Melalui Permainan Ludo Geometri Di Paud Habibul Ummi Ii.” SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS) 1, no. 1 (2013): 250. https://doi.org/10.24036/spektrumpls.v1i1.1537. Kadir, Mohd Nazir, Mif Rohim Noyo Sarkun, Nur Zainatul Nadra Zainol, and Mohd Amin Mohd Yunus. “A Systematic Analysis on Wujuh Qira’at in Ablution’s Verses and Its Implication to the Islamic Law for Recognition System.” Journal of Quranic Sciences and Research 1, no. 1 (2020): 11–19. https://doi.org/10.30880/jqsr.2020.01.01.002. Karimi, Fatemh, and Mohammad Jafari Harandi. “A Comparative Study of Reason in Islamic Education with Emphasis on Imami and Sunni Jurisprudence.” Iranian Journal of Comparative Education 4, no. 1 (2021): 1047–63. https://doi.org/10.22034/IJCE.2021.233757.1165. Khalil, M A E. "The Qur'anic Qiraat from the Companions Which Appear to Be Different Do Not Imply That the Qur'an Has Not Been Preserved. Surah Al-Jumu'ah, Verse 9 as a …," 2022. https://thesiscommons.org/jsgvr/download?format=pdf. Laksana, Andri Winjaya, Hartiwiningsih Hartiwiningsih, Hari Purwadi, and Anis Mashdurohatun. “The Sufism Healing As an Alternative Rehabilitation for Drug Addicts and Abusers.” Qudus International Journal of Islamic Studies 11, no. 1 (2023): 149–76. https://doi.org/10.21043/qijis.v11i1.15025. Latif, Mohd Abdul Nasir Abd, Ahmad Zulfiqar Shah Abdul Hadi, Muhammad Hasbi Abdul Rahman, Muhammad Nadzir Ibrahim, and Muhammad Akramin Kamarul Zaman. “Implimentasi Talaqqi Dan Mushafahah Dalam Pengajaran Dan Pembelajaran Qira’at Warsh ‘An Nafi.’” O-JIE: Online Journal of Islamic Education 5, no. 1 (2017): 28–38. https://ojie.um.edu.my/index.php/O-JIE/article/view/5237. Muhammad, Husen. “Metode Musyafahah Untuk Meningkatkan Kemampuan Membaca Al-Qur’an Siswa SMP-IT As-Salam Ambon.” Jurnal Pendidikan 14, no. 2 (2022): 267–88. https://e-jurnal.iainsorong.ac.id/index.php/Al-Riwayah%0AMetode. Muhyin, Nabila Fajriyanti, Velida Apria Ningrum, and Ach. As’ad Abdul Aziz. “The Activity of Sab’u Al-Munjiyat Recitation on TMI Al-Amien Prenduan Islamic Boarding School for Girls: The Perspective of Anthropology Theory.” Al-Qudwah 2, no. 2 (2024): 220–35. https://doi.org/10.24014/alqudwah.v2i2.29272. Mujib, Ahmad, and Marhamah Marhamah. “Al-Quràn Learning Innovation Based on Blended Cooperative e-Learning in School.” Journal of Educational and Social Research 10, no. 4 (2020): 47–54. https://doi.org/10.36941/JESR-2020-0063. Mustofa, Bisri. Al-Ibris. kudus, Jawa Tengah: Maktabah Menara Kudus, 2016. Nadhiran, Hedhri. “Kritik Sanad Hadis: Tela’ah Metodologis.” Jurnal Ilmu Agama 2, no. 1 (2017): 1–14. https://jurnal.radenfatah.ac.id/index.php/JIA/issue/view/87. Nur, Lutfi, Anne Hafina, and Nandang Rusmana. “Kemampuan Kognitif Anak Usia Dini Dalam Pembelajaran Akuatik.” Scholaria: Jurnal Pendidikan Dan Kebudayaan 10, no. 1 (2020): 42–50. https://doi.org/10.24246/j.js.2020.v10.i1.p42-50. Purnamasari, Nia Indah. “Konstruksi Sistem Pendidikan Pesantren Tradisional Di Era Global : Paradoks Dan Relevansi Nia Indah Purnamasari” 6 (2016). https://doi.org/https://doi.org/10.54180/elbanat.2016.6.2.73-91. Purwowidodo, Agus, and Muhamad Zaini. “Developing a Value-Based Moderate Islamic Education Model: A Case Study of Pesantren Sidogiri Pasuruan.” Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies) 12, no. 1 (2024): 43–62. https://doi.org/10.15642/jpai.2024.12.1.43-62. Putri, Habibah Afiyanti, Riris Wahyuningsih, and Fitriatul Masruroh. “Developing Children’s Memory in Memorizing the Qur’an Juz 30 Using Talaqqi Method for 5-6 Year-Old Children at Taman Qur’an Kindergarten Banyuwangi.” ICHES: International Conference on Humanity Education and Social 2, no. 1 (2023): 11. https://proceedingsiches.com/index.php/ojs/issue/view/2. Rohman, Thofiqur, Ulul Huda, and Hartono. “Methodology of Hadith Research : The Study of Hadith Criticism Metode Penelitian Hadis : Studi Tentang Kritik Hadis.” Journal of Hadith Studies 2, no. 1 (2019): 73–84. Rosidi. KH. Arwani Amin: Penjaga Wahyu Dari Kudus. Kudus: al-Makmun, 2008. Royyanah, Ni’matur, and Aris Adi Leksono. “Qiroati Method Program Management in Developing the Quality of Quran Reading for Students.” Chalim Journal of Teaching and Learning 4, no. 1 (2024): 23–29. https://doi.org/10.31538/cjotl.v4i1.1108. Sholahudin, M. Ulama Penjaga Wahyu. Kediri, Jawa Timur: Pustaka Zam-Zam, 2017. Sholihah, Nikmatus, and Nia Indah Purnamasari. “Metode Musyafahah Sebagai Solusi Mempermudah Anak Usia Dini Menghafal” 10, no. 20 (2020). https://doi.org/https://doi.org/10.54180/elbanat.2020.10.2.280-300. Siregar, Dzulhajj ‘Aeyn Abe. “Ex Post Facto Dari Implementasi Program Tahfiz Al-Qur’an Dengan Metode Talaqqi Dan Musyafahah Melalui Target Hariandi Smp It Ad Durrah.” Jurnal Tinta 4, no. 2 (2022): 39–51. Smith, Graeme D., and Debra Jackson. “Integrity and Trust in Research and Publication: The Crucial Role of Peer Review.” Journal of Advanced Nursing 78, no. 11 (2022): e135 36. https://doi.org/10.1111/jan.15438. Suriansyah, Muhammad Arsyad. “Implementasi Metode Talaqqi Dan Musyafahah Dalam Meningkatkan Kemampuan Membaca Al-Qur’an Siswa Di SD Swasta Salsa.” Fitrah Journal Islamic of Education 1, no. 2 (2020). https://doi.org/https://doi.org/10.53802/fitrah.v1i2.27. Suriansyah, Muhammad Arsyad, Universitas Islam, Negeri Sumatera, and Utara Medan. “Implementasi Metode Talaqqi Dan Musyafahah Dalam Meningkatkan Kemampuan Membaca Al- Qur’an Siswa” 1, no. 2 (2020): 216–31. https://doi.org/https://doi.org/10.53802/fitrah.v1i2.27. Susanto, Roni, and Muhammad Afif Ulin Nuhaa. “Menjaga Autentitas Bacaan Al-Qur’an Di Pesantren Al-Hikmah Purwoasri Kediri.” Integratia: Journal of Education, Human Development, and Community Engagement 1, no. 2 (2023): 143–52. https://ojisnu.nuponorogo.or.id/index.php/integratia/article/view/42. Susanto, Roni, and Sugiyar. “Implementation of Mutammimah Book Learning on the Reading Ability of Kutub Al-Turats at Madrasah Riyadlotusy Syubban Ponorogo.” Edukasi Lingua Sastra 21, no. 1 (2023): 207–2017. https://doi.org/https://doi.org/10.47637/elsa.v21i2.667. Susanto, Roni, Wahyu Widodo, and Nur Kolis. “The Implication of the Sima’an Ahad Pahing on the Qur’an Memorization at PPTQ Al-Hasan Ponorogo.” Jurnal Kebudayaan 18, no. 2 (2023): 125–32. https://doi.org/10.37680/adabiya.v18i2.2396. Susanto, Roni, Robbin Dayyan Yahuda, Basuki, and Abdul Kadir. "Implications of Developing Fayd Al-Barakat Book on Learning Qiraat Sab'ah in the Digital Era." Jurnal Pendidikan Al-Ishlah 15, no. 4 (2023). https://doi.org/https://doi.org/10.35445/alishlah.v15i4.3009. Taftahi, Jannat. "Quranic Sciences from Abdul Hamid Farahi's Perspective ( 1863-1930 )." International Journal of Applied Linguistics & English Literature 2, no. 1 (2017). www.ijalel.aiac.org.au. Taşkın, Ferhat. "Could Avicenna's God Remain within Himself? A Reply to the Naṣīrian Interpretation.” International Journal for Philosophy of Religion 23, no. 1 (2024). https://doi.org/10.1007/s11153-024-09918-0. Ulya, Muhim Nailul, and Syed Abdul Rahman Alkafi. "An Analysis of the Sanad Transmission by K H Muhammad Arwani ( 1905 – 1994 ) and His Role in the Dissemination of Qiraat Sab ' Ah Knowledge in Indonesia." Qof: Jurnal Studi Al-Qur’an Dan Tafsir 7, no. 2 (2024): 245–62. https://doi.org/10.30762/qof.v7i2.1400.Nailul. Yahuda, Robbin Dayyan, Roni Susanto, Wahyu Widodo, Nur Kolis, and Bagas Abdillah. “Musafahah Method Transformation on Learning Qiraah Sab’ah in PPTQ Al-Hasan Ponorogo.” Masdar Jurnal Studi Al-Qur’an & Hadis 5, no. 2 (2023). https://doi.org/https://doi.org/10.15548/mashdar.v5i2.7293. Yang, Zhi Hong, Hiroko Miyahara, Jiro Takeo, and Masashi Katayama. “Erratum: Ingestion of a Single Serving of Saury Alters Postprandial Levels of Plasma n-3 Polyunsaturated Fatty Acids and Long-Chain Monounsaturated Fatty Acids in Healthy Human Adults.” Lipids in Health and Disease 11 (2012): 1–2. https://doi.org/10.1186/1476-511X-11-151. Zaini, Hafidh, Wahyu Andi Saputra, and Ary Mutawalie. “Implementasi Metode Pengajaran Qiraat Sab’ah Di Pondok Pesantren Al-Qur’an Asy Syifa.” Mumtaz:Jurnal Pendidikan Agama Islam 1 (2022): 99–107. https://www.ejournal.iaiibrahimy.ac.id/index.php/mumtaz/issue/view/100.